Knowledge, perception and experiences of school-aged children with siblings going through cancer - Coroza, Charisma Amor A.; Simoy, Arriane April E.; Roldan, Aurorita T. (2010.)
This study explored the knowledge, perceptions, and experiences of school-aged children with siblings going through cancer. Qualitative research method was used in conducting this study. Twenty six children ages 7 to 13 years old which have siblings diagnosed with cancer were gathered through purposive sampling. They were interviewed using open-ended questions that were structured by researchers. A qualitative approach was used to analyze the data; profiling the thematic analysis were done to find trends and patterns from the answers given by the respondents. Statistical techniques such as frequency and percentage were also used. Findings revealed that children ages 11-13 years old have broader knowledge of their sibling's illness. Perceived effects of illness showed closer relationship. Personal and family-related problems were seen as most evident challenges for the children. This study suggests that financial and emotional support should be given to families with children diagnosed with cancer.
Thesis (BSFLCD)--University of the Philippines Diliman.
Keywords: Children -- Philippines